2008
DOI: 10.1017/s0022112008001481
|View full text |Cite
|
Sign up to set email alerts
|

Variable-density mixing in buoyancy-driven turbulence

Abstract: The homogenization of a heterogeneous mixture of two pure fluids with different densities by molecular diffusion and stirring induced by buoyancy-generated motions, as occurs in the Rayleigh–Taylor (RT) instability, is studied using direct numerical simulations. The Schmidt number, Sc, is varied by a factor of 20, 0.1 ≤ Sc ≤ 2.0, and the Atwood number, A, by a factor of 10, 0.05 ≤ A ≤ 0.5. Initial-density intensities are as high as 50% of the mean density. As a consequence of differential accelerations experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 32 publications
7
124
0
Order By: Relevance
“…The asymmetry in Fig. 15 might be also attributed to light fluid mixing more rapidly than heavier fluid, similar to the observation reported by Livescu and Ristorcelli [52] . Since the molecular mixing increases during the deceleration period, the asymmetry becomes more pronounced by the end of deceleration period.…”
Section: Spatial Profilessupporting
confidence: 88%
“…The asymmetry in Fig. 15 might be also attributed to light fluid mixing more rapidly than heavier fluid, similar to the observation reported by Livescu and Ristorcelli [52] . Since the molecular mixing increases during the deceleration period, the asymmetry becomes more pronounced by the end of deceleration period.…”
Section: Spatial Profilessupporting
confidence: 88%
“…That the anisotropy increases with wavenumber is perhaps counterintuitive, and perhaps contradictory to the notion of small-scale isotropy. This was first pointed out by Livescu & Ristorcelli (2008) and further discussed by Livescu et al (2009 (no summation), but found that, with this measure, the small scales were isotropic. A question then arises as to why the velocity-anisotropy parameter increases in the viscosity-dominated range 10 −1 < k r η < 2.…”
Section: Subgrid Extensions Of Planar Spectramentioning
confidence: 81%
“…The CFDNS code also uses a mixed spectral-compact finite differences scheme. DNS of HRT are reported in references [1,[90][91][92][93] (A up to 0.5) for the unsteady case and reference [16] for the stationary case (A up to 0.9). LES of incompressible RTI using explicit subgrid modelling were performed with the MIRANDA code in reference [94] at A = 0.5 and of stationary HRT using the stretched vortex model of Pullin [95] in reference [16] at A up to 0.9.…”
Section: (I) Direct Numerical Simulations Of Rayleigh-taylor Instabilmentioning
confidence: 99%
“…A comprehensive discussion of these metrics, including rigorous bounds, can be found in reference [92]. Thus, the usual mix measure θ = f 1 f 2 /F 1 F 2 depends on the mean and variance of the density.…”
Section: (I) Direct Numerical Simulations Of Rayleigh-taylor Instabilmentioning
confidence: 99%